2014
DOI: 10.1002/lary.24925
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive primary olfactory neuroblastoma of the sphenoclival region: A case report and literature review

Abstract: Olfactory neuroblastoma (ONB) is an uncommon malignant tumor of neural crest origin, which commonly arises in the superior nasal cavity. Ectopic origin of an ONB is exceedingly rare. We describe a rare case of an ectopic sphenoclival ONB with extensive involvement of the central skull base and with development of systemic metastases. To our knowledge, ours is the first case that describes the imaging features of this rare entity on computed tomography (CT), magnetic resonance imaging, 18 F-fluorodeoxyglucose-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
(110 reference statements)
1
9
0
Order By: Relevance
“…Recent studies have shown that olfactory neuroepithelium also is dispersed throughout the superior turbinate, middle turbinate, and the nasal cavity . That 48% of tumors in our study involved the skull base or the mucosa abutting the skull base, along with the numerous reports of ectopic origins of ONB, is confirmation of this. Resection of the dura can be associated with significant morbidity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recent studies have shown that olfactory neuroepithelium also is dispersed throughout the superior turbinate, middle turbinate, and the nasal cavity . That 48% of tumors in our study involved the skull base or the mucosa abutting the skull base, along with the numerous reports of ectopic origins of ONB, is confirmation of this. Resection of the dura can be associated with significant morbidity.…”
Section: Discussionsupporting
confidence: 89%
“…It arises from the olfactory neuroepithelium in the superior portion of the nasal vault and cribriform plate . Although some investigators assert that the diagnosis should be based on involvement of the cribriform plate, others have reported ectopic origins in the lower nasal cavity, paranasal sinuses, intracranially, or in the sella turcica . Open craniofacial resection has long been the gold standard treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory neuroblastoma (ONB) is also called esthesioneuroblastoma, which is a rare and slow-growing malignant tumor arising in the olfactory epithelium located in the upper part of nasal cavities, the ectopic sphenoclival part, 1 or the sphenoid sinus. 2 ONB comprises 3% to 5% of nasal cancers with an incidence of 1 per 2.5 million.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the alternative origin hypotheses, like Jacobson’s vomero-nasal organ or autonomic ganglia, support the concept of ectopic origin of ONB. Ectopic ONBs are particularly rare and have been previously reported in 21 cases, such as atypical nasal cavity locations, paranasal sinuses, nasopharynx, petrous apex, pituitary gland, sphenoclival region, and pterygopalatine fossa [ 8 11 ]. Only 1 multifocal synchronous ONB case besides ours has been documented in the literature [ 12 ].…”
Section: Discussionmentioning
confidence: 99%